Exploring the roles of counselors in addressing challenges faced by sexually abused children: a case of Family Support Trust Chitungwiza Hospital. - Zifa, Yolanda (Midlands State University, 2019)
The study sought to explore the roles of counsellors in addressing challenges faced by sexually abused children. With the rise of child abuse cases each year, counsellors are believed to have an essential role to play in assisting the abused children. Qualitative methodology was employed to gather data from counsellors at Chitungwiza hospital Family Support Trust. Semi-structured interviews were the method used in the study for data collection. A phenomenological research design was used. Purposive sampling was also used in selecting the participants for the research. Thematic analysis was used to analyse the data and data was presented in sets of themes which helped further explore and answer formulated research questions regarding the roles of counsellors. Generally the findings demonstrated that besides challenges faced by counsellors in addressing challenges faced by sexually abused children, counsellors are continuously playing an essential role in providing services to sexually abused children. The conclusion derived was that counsellors have a greater role to play in addressing challenges faced by sexually abused children. Structure agency employed in this study assists one to explain that counsellors as well as abused children are affected by the society.